Effects of continuous positive airway pressure on systemic inflammation in patients with moderate to severe obstructive sleep apnoea: a randomised controlled trial. Issue 1 (11th September 2008) - Kohler, M; Ayers, L; Pepperell, J C T; Packwood, K L; Ferry, B; Crosthwaite, N; Craig, S; Siccoli, M M; Davies, R J O; Stradling, J R
Abstract : Background: Obstructive sleep apnoea syndrome (OSAS) has been associated with cardiovascular disease in epidemiological and observational studies. Continuous positive airway pressure (CPAP) is the treatment of choice for OSAS, but the impact of this intervention on systemic inflammation involved in the atherosclerotic process remains unclear. Methods: 100 men with moderate–severe OSAS were randomised to therapeutic (n = 51) or subtherapeutic (n = 49) CPAP treatment for 4 weeks to investigate the effects of active treatment on inflammatory markers such as highly sensitive C reactive protein (hsCRP), interleukin (IL)6, interferon γ (IFNγ) and anti-inflammatory adiponectin. Results: 4 weeks of therapeutic CPAP did not significantly change blood levels of hsCRP compared with the subtherapeutic control group (difference between median changes −0.24 mg/l (95% CI −0.88 to +0.24); p = 0.30). Plasma levels of IL6 and IFNγ did not change significantly following therapeutic compared with subtherapeutic CPAP (difference between median changes +0.52 and −0.07 pg/ml (95% CI −0.72 to +1.94 and −0.81 to +0.44); p = 0.45 and p = 0.82, respectively). Furthermore, 4 weeks of therapeutic CPAP did not significantly change levels of adiponectin in plasma compared with the subtherapeutic control group (difference between median changes +0.05 pg/ml (95% CI −0.36 to +0.47); p = 0.84). If patients with hsCRP values above 8 mg/l at baseline were excluded, differences between the changes in hsCRP, IL6, IFNγ and adiponectin after 4 weeks of CPAP were smaller, and again not statistically different between groups. Conclusions: 4 weeks of CPAP treatment has no beneficial effect on blood markers of inflammation and adiponectin in patients with moderate–severe obstructive sleep apnoea.